Metabolic crisis occurs with seizures and periodic discharges after brain trauma. Issue 4 (28th February 2016) - Vespa, Paul; Tubi, Meral; Claassen, Jan; Buitrago‐Blanco, Manuel; McArthur, David; Velazquez, Angela G.; Tu, Bin; Prins, Mayumi; Nuwer, Marc
Abstract : Objective: Traumatic brain injury (TBI) results in persistent disruption of brain metabolism that has yet to be mechanistically defined. Early post‐traumatic seizures are one potential mechanism for metabolic crisis and hence could be a therapeutic target. We hypothesized that seizures and pseudoperiodic discharges (PDs) may be mechanistically linked to metabolic crisis as measured by cerebral microdialysis. Methods: A prospective multicenter study of surface and intracortical depth electroencephalography (EEG) was performed in conjunction with cerebral microdialysis in a cohort of severe TBI patients with time‐locked analysis of the neurochemical response to seizures and pseudoperiodic discharges. Results: Seizures or PDs occurred in 61% of 34 subjects, with 42.9% of these seizures noted only on intracortical depth EEG and in some cases lasting for many hours. Metabolic crisis as measured by elevated cerebral microdialysis lactate/pyruvate ratio occurred during seizures or PDs but not during electrically nonepileptic epochs. Interpretation: In TBI patients, seizures and periodic discharges are one mechanism for metabolic crisis, and hence represent a therapeutic target for future study. Ann Neurol 2016;79:579–590